Regional innovation support systems in South Korea and Germany compared - Hassink, Robert (ERDKUNDE, 2004)
Since the beginning of the 1990s, one can observe a clear shift in the aims of regional policy in industrialised countries from reducing regional inequalities to developing endogenous small and medium-sized enterprises (SMEs) and innovation in regions through regional innovation support systems. Innovation support systems are defined as a group of actively co-operating organisations that support the innovativeness of SMEs. An innovation support system consists of all agencies found in three support stages, namely the provision of general information, technological advice and joint research and development (R&D) projects, between SMEs and higher education institutes (HEIs) and public research establishments (PREs). Agencies found in these stages try to help to solve innovation problems mainly of technology-following SMEs by either giving them advice themselves or by referring them to other agencies in a further stage of support. This paper aims at comparing these regional innovation support systems in South Korea and Germany, concerning the instruments used, their impact on regional economic development, their level of institutional embeddedness in regions and the ability of regions to co-ordinate innovation support policies. The main conclusions of the paper are that there are similarities between the regional innovation support systems found in both countries when it comes to policy instruments, but that the countries differ concerning their level of institutional embeddedness and the abilities of regions to co-ordinate innovation support policies. The paper also tentatively concludes that in countries where regions have the ability to co-ordinate policies into integrative innovation support systems, the impact on regional economic development tend to be larger than in countries where these abilities are lacking, that is where dirigiste and grassroots support systems prevail.